Physicochemical characterization and oxidative stability of microencapsulated edible sacha inchi seed oil by spray drying - Landoni, L. (2020)
The aim of this work was to obtain sacha inchi oil (SIO) microcapsules from two different species, Plukenetia volubilis L. (SIVO) and Plukenetia huayllabambana L. (SIHO), using different biopolymers as wall materials and spray drying technology. The physicochemical characteristics such as encapsulation efficiency, particle size, morphology and oxidative stability were analyzed in order to select the best formulation that could potentially be used as an ingredient in the development of functional food. Bulk SIO and four formulations were tested for each oil ecotype, using different encapsulating agents: maltodextrin (MD), Arabic gum (AG), whey protein concentrate (WPC) and modified starch HI-CAP®-100 (H). Microcapsules made of H presented the highest oxidative stability and encapsulation efficiency compared to AG, AG:MD or AG:MD:WPC formulations.